Effects of Work on Blood Glucose, Triglycerides and Lactic Acid Concentrations of the Bali Cattle - W. Sayang Yupardhi (Faculty of Animal Science, Universitas Gadjah Mada, 2000)
Artikel dalam bentuk PDF